2017
DOI: 10.1371/journal.pone.0178076
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional government cash transfers in support of orphaned and vulnerable adolescents in western Kenya: Is there an association with psychological wellbeing?

Abstract: BackgroundOrphaned and vulnerable adolescents (OVA) in sub-Saharan Africa are at greater risk for adverse psychological outcomes compared with their non-OVA counterparts. Social interventions that provide cash transfers (CTs) have been shown to improve health outcomes among young people, but little is known about their impact on the psychological wellbeing of OVA.ObjectiveAmong OVA in western Kenya, we assessed the association between living in a household that received monthly unconditional government CTs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…First, being able to pay the rent has a positive impact on recipients' own perceptions of their mental well‐being, for both men and women. Studies on cash transfers have shown that this type of social protection instrument can improve mental health and reduce stress and depressive symptoms (Haushofer and Shapiro, ) and have positive impacts on beneficiaries' psychosocial well‐being (Attah et al, ; Samuels and Stavropoulou, ; Shangani et al, ). Similarly, UNICEF's assessment of its child cash grant (CCG) for Syrian refugees reported that “one of the most notable outcomes of the focus group discussions is the number of participants that felt the child grant had a positive impact on their psychological state as well as that of other family members” (UNICEF, , p. 21).…”
Section: Effects Of the Cash Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…First, being able to pay the rent has a positive impact on recipients' own perceptions of their mental well‐being, for both men and women. Studies on cash transfers have shown that this type of social protection instrument can improve mental health and reduce stress and depressive symptoms (Haushofer and Shapiro, ) and have positive impacts on beneficiaries' psychosocial well‐being (Attah et al, ; Samuels and Stavropoulou, ; Shangani et al, ). Similarly, UNICEF's assessment of its child cash grant (CCG) for Syrian refugees reported that “one of the most notable outcomes of the focus group discussions is the number of participants that felt the child grant had a positive impact on their psychological state as well as that of other family members” (UNICEF, , p. 21).…”
Section: Effects Of the Cash Transfermentioning
confidence: 99%
“…Only a few studies have analysed the effect of cash transfers on the mental well‐being of populations that suffer poverty‐induced stress stemming from their lack of capacity to meet even their most immediate needs. Shangani et al (), for example, analysed the psychological outcomes of unconditional cash transfer programmes on the mental health of orphans and vulnerable adolescents (OVA) in Kenya and found that OVAs living in households that received the cash transfer were less likely to have anxiety and PTSD than those living in non‐recipient households, and youths living in recipient households were 24 per cent less likely to suffer depression. Although poverty and mental health are closely linked and increase vulnerability, the psychological outcomes of cash transfers on the poor – as well as refugees – are understudied.…”
Section: The Potential Of Cash Transfers To Facilitate Improvements Imentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Future research should determine whether there is a threshold or tipping point to achieve changes in mental wellbeing from cash assistance programming, as other studies have largely shown positive improvements. [40] For instance, a study in Kenya assessed the mental health effects of cash by testing participant levels of the stress hormone cortisol. Results from cortisol testing demonstrated no meaningful change overall, 17 but sub-analyses revealed additional details of how program design can affect the impact of cash on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of posttraumatic stress disorder in the general population. Stansfeld et al [48] used the Harvard Trauma Questionnaire (HTQ) in a sample of 1 034 Grade 8 students (mean age 14.2) from Cape Town, South Africa and reported a prevalence for PTSD of 21.5%. The study found that those falling in the highest quartile of violence were most likely to score positive for symptoms of PTSD.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%